2014
DOI: 10.1371/journal.pone.0109909
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Hand Illusion Reduces Discomfort Caused by Cold Stimulus

Abstract: There is a growing interest in body-ownership disruptions and their consequences for subjective experiences such as tactile sensations or pain. Here, we investigated the effect of the rubber hand illusion (RHI) on the perceived discomfort caused by cold stimulus applied to the real hand. The results showed reduced discomfort to cold reflected in behavioural and subjective measures. The stronger the illusion, the later the cold temperature became unpleasant and the less intense the experience was rated. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Mohan and coworkers 40 showed no changes in pain perception during the rubber hand illusion , so that the analgesic effects of looking at one's own body would not hold true when the body part is fake, even though it is attributed to oneself. In contrast, other studies showed that during the rubber hand illusion the vision of the "owned" rubber hand leads to an increase in HTP 19 and higher resistance to painfully cold stimuli 16,54 . This held true for a virtual arm, since Martini and coworkers 36 To understand these different findings we looked into the methodological differences between these studies.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mohan and coworkers 40 showed no changes in pain perception during the rubber hand illusion , so that the analgesic effects of looking at one's own body would not hold true when the body part is fake, even though it is attributed to oneself. In contrast, other studies showed that during the rubber hand illusion the vision of the "owned" rubber hand leads to an increase in HTP 19 and higher resistance to painfully cold stimuli 16,54 . This held true for a virtual arm, since Martini and coworkers 36 To understand these different findings we looked into the methodological differences between these studies.…”
Section: Introductionmentioning
confidence: 81%
“…The distance between real and fake limb has been identified as critical factor for body ownership, in the vertical 27 and in the horizontal plane 22 . On the other hand, body ownership over a fake body part seems to affect pain perception 16,19,36,54 .…”
Section: Introductionmentioning
confidence: 99%
“…This is reminiscent of the so-called rubber hand illusion (RHI, Botvinick and Cohen, 1998), in which perceived ownership over an artificial limb can be induced via the congruence of vision and touch. There is evidence that the RHI may reduce pain (Heged€ us et al, 2014;Martini et al, 2014;Siedlecka et al, 2014). It remains to be shown to what extent some of the divergent results can be explained by methodological differences (Mohan et al, 2012;Nierula et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found in a study investigating the effects of the RHI on the perceived discomfort caused by cold stimuli. In their experiment, Siedlecka and colleagues applied ice on the hand of their participants, right after the induction of the RHI (Siedlecka, Klimza, Łukowska, & Wierzchoń , 2014). Two distinct groups of participants were considered, one experimental group where the stroking to induce the illusion was timely and spatially synchronized, and a control group where the stroking was spatially incongruent.…”
Section: Rubber Hand Illusion and Painmentioning
confidence: 99%